2022
DOI: 10.3390/nu15010119
|View full text |Cite
|
Sign up to set email alerts
|

UPLC-MS/MS Analysis of Naturally Derived Apis mellifera Products and Their Promising Effects against Cadmium-Induced Adverse Effects in Female Rats

Abstract: Honeybee products arouse interest in society due to their natural origin and range of important biological properties. Propolis (P) and royal jelly (RJ) attract scientists’ attention because they exhibit antioxidant, anti-inflammatory, anti-bacterial, anti-tumor, and immunomodulatory abilities. In this study, we tested whether P and RJ could mitigate the adverse effects of cadmium (Cd) exposure, with particular emphasis on the reproductive function in female rats. In this line, one week of pretreatment was est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…The ProteoWizard suite's MS Convert was employed to transform raw data files into the mzXML format. The online technique of Global Natural Products Social Molecular Networking (GNPS) was used to establish molecular networking, with a precursor mass tolerance of 2.0 Da, the fragment ion mass tolerance set to 0.5 Da, and a cosine score of 0.7 [35] . Cytoscape 3.5.1 (https://cytoscape.org/, access on November 12, 2023) was used to display the spectral networks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ProteoWizard suite's MS Convert was employed to transform raw data files into the mzXML format. The online technique of Global Natural Products Social Molecular Networking (GNPS) was used to establish molecular networking, with a precursor mass tolerance of 2.0 Da, the fragment ion mass tolerance set to 0.5 Da, and a cosine score of 0.7 [35] . Cytoscape 3.5.1 (https://cytoscape.org/, access on November 12, 2023) was used to display the spectral networks.…”
Section: Methodsmentioning
confidence: 99%
“…The online technique of Global Natural Products Social Molecular Networking (GNPS) was used to establish molecular networking, with a precursor mass tolerance of 2.0 Da, the fragment ion mass tolerance set to 0.5 Da, and a cosine score of 0.7. [35] Cytoscape 3.5.1 (https://cytoscape.org, access on November 12, 2023) was used to display the spectral networks. The databases Sci-Finder, PubMed, and Google Scholar were utilized to verify the metabolites, as well as the website for the Dictionary of Natural Products.…”
Section: Chemical Profile Of Apilarnilextracts Using Ltq-uplc-ms-msmentioning
confidence: 99%
“…The beneficial properties include antioxidant, antibacterial, antifungal, and hepatoprotective [ 241 , 249 ]. A recent study by Amr et al [ 250 ] on female rats showed that boneybee products had the potential to reduce oxidative stress, increase cadmium (Cd) excretion via the kidneys, and modify intestinal absorption of the metal.…”
Section: Medicinal Uses Of Common Edible Insectsmentioning
confidence: 99%
“…Additionally, MSConvert from the ProteoWizard suite (https://proteowizard.sourceforge.io/ download.html; accessed on 25 December 2022) was used to convert the raw data files to mzXML format. The molecular network was created using the global natural products social molecular networking (GNPS) online workflow [42,49]. The spectra from the network were then verified against GNPS's spectral libraries and literature data.…”
Section: Chemical Identification Of the Compounds Using Lc-ltq-ms-msmentioning
confidence: 99%
“…The purpose of this research was to identify Sidr honey samples from Egypt and Saudi Arabia based on physicochemical qualities utilizing modern techniques, i.e., HPLC, LC-MS/MS, NMR, and SPME-GC-MS as part of our ongoing project, with particular emphasis on honeybees and bee products [35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%